Vibration control of civil engineering structures using magneto-rheological dampers - Braz-César, M.T. (2015)
Recent developments in civil engineenng stmctures design and constmction allowed the creation of slender and flexible stmctures such as towers, high-rise buildings and long span bridges. The structural properties of these stmctures, namely the low damping capability makes them vulnerable to strong wind or earthquake actions. In recent decades various control systems based on passive, active, semi-active and hybrid devices have been proposed and different control strategies were developed and implemented for structural vibration control. Among these, lhe semi-active based control hás become an important altemative to passive and active control methods as a result of its ability to gather some of the advantages of the passive control such as the reliability of these systems with the adaptability of the active control.